Effects of combined pulsed electric fields and mild temperature pasteurization on microbial inactivation and physicochemical properties of cloudy red apple juice (Malus pumila Niedzwetzkyana (Dieck)) - Katiyo, Wendy; Yang, Ruijin; Zhao, Wei (Journal of food safety, 2017)
The influence of combined pulsed electric fields (PEF) and mild temperature on the inactivation of Escherichia coli, Salmonella enteritidis, and Saccharomyces cerevisiae suspended in a novel cloudy red apple juice (Malus pumila Niedzwetzkyana (Dieck)) was investigated to define treatment conditions that meet the U.S. Food and Drug Administration (FDA) regulation for fruit juice pasteurization. There was significant microbial inactivation (p < .05) with increased experimental treatment conditions (electric field strength: 25–35 kV/cm, treatment time: 86–258 µs, post‐treatment temperature: 30–50 °C). The highest level of inactivation for E. coli, S. enteritidis, and S. cerevisiae was 5.21, 6.02, and 5.49 log reduction, respectively. PEF treatment at 35 kV/cm for 258 µs combined with heating at 50 °C was selected as pasteurization conditions. Pasteurization did not cause significant changes (p < .05) in pH, titratable acidity, total soluble solids, conductivity, and particle size of cloudy red apple juice, in comparison with conventional treatment. Practical applications Red‐fleshed apples are increasingly becoming a subject of interest in the fruit industry due to their remarkable anthocyanin content. However, mere identification or development of novel fruits is insufficient for the fruit juice industry to cater for consumer demand. There is need to combine this with novel processing technologies that ensure preservation of the desired unique quality attributes. This study indicated that combined PEF and mild heat can be successfully applied for the pasteurization of a novel cloudy red apple juice without significantly affecting important juice properties such as pH, acidity, conductivity, and particle size. This work provides a basis for new product development as numerous red‐fleshed apple cultivars are being developed and PEF technology is progressing toward industrial application.